The overlooked role of uterine fibroids in primary infertility in Pakistan - Rani, Susheeta; Sohaib, Asharib; Balach, Rahul (Journal of the Pakistan Medical Association, 2026)
Dear Editor, According to the World Health Organization, one in six people of reproductive age are affected by infertility. Infertility can be classified as primary, where a person has never conceived, or secondary, where a pregnancy has occurred at least once.[1] Pakistan, despite being one of the most populous countries, faces a significant infertility challenge, with 21.9% of couples unable to conceive. Women account for a major share of infertility cases.[2] A survey conducted in Punjab further highlighted that 12.6% of women reported experiencing primary infertility.[3] This raises questions about underlying causes, including the role of uterine fibroids in contributing to primary infertility in Pakistan. A cross-sectional study conducted in Gujrat, Pakistan, identified submucosal fibroids, a specific type of uterine fibroid, as the leading cause of infertility among young women.[4] Similarly, research carried out at a hospital in Hyderabad reported a notably high infertility rate of 27.4% among women with uterine fibroids who had no history of prior pregnancies.[5] This data emphasises the strong association between uterine fibroids and infertility, particularly in younger women, indicating the significant reproductive challenges posed by fibroid-related complications in this population. Primary infertility in Pakistan is a multifaceted issue influenced by a complex interplay of factors, including limited access to healthcare services, inadequate education about reproductive health, hormonal imbalances, and cultural stigmas. A lack of comprehensive education about reproductive well-being, including the importance of regular check-ups, contraception, and fertility awareness, is an important contributing factor. Many women in Pakistan, especially those from low-income backgrounds, are unable to avail quality healthcare facilities due to the high cost of medical treatment and societal norms. This limited access to healthcare services can lead to delayed or inaccurate diagnosis of uterine fibroids, which, in turn, can result in primary infertility. Hormonal imbalances, such as those associated with polycystic ovary syndrome (PCOS), can also contribute to primary infertility. Cultural taboos and discrimination surrounding infertility can further exacerbate these challenges, as the fear of social ostracism may discourage women from seeking help or discussing their reproductive health concerns. While a multitude of factors influence primary infertility in Pakistan, uterine fibroids emerge as a particularly significant cause. Addressing primary infertility in Pakistan requires a comprehensive approach that tackles other underlying factors while prioritising the prevention, diagnosis, and treatment of uterine fibroids.